Educational Software and Security Vulnerabilities: an experimental study - Rossi, Diego; Bressan, Lucas; Campos, Fernanda; Oliveira, André; Ströele, Victor (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2023: Anais do XXXIV Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/sbie.2023.234860, 2023)
The educational domain comprises fragmented solutions with different services, tools, and plugins. As a complex system, it raises several security and threat prevention concerns. We conducted an exploratory study to characterize security vulnerabilities and their impacts on Learning Management Systems. We focus on an intelligent educational solution using the risk assessment methodology HEAVENS 2.0. We identify vulnerabilities in architectural elements and detail two of them. Risks are not acceptable, and security measures must be adopted to avoid damage to students, tutors, and teachers. The results highlight the security vulnerabilities and the consequences of threats to users, hoping to motivate future research